Safety nets in Africa : effective mechanisms to reach the poor and most vulnerable - Del Ninno, Carlo; Mills, Bradford F. (Africa development forum., 2015)
The need for safety nets in Sub-Saharan Africa is vast. In addition to being the world's poorest region, Sub-Saharan Africa is also one of the most unequal. In this context, redistribution must be seen as a legitimate way to fight poverty and ensure shared prosperity - and all the more so in countries where growth is driven by extractive industries that are not labor-intensive and often employ very few poor people. Given that most African countries face difficult decisions about how to allocate limited resources among a number of social programs, evidence is important. Do Safety Net programs.